Nutrients Supplementation through Organic Manures Influence the Growth of Weeds and Maize Productivity - Ghosh, Dibakar; Brahmachari, Koushik; Skalicky, Milan; Hossain, Akbar; Sarkar, Sukamal; Dinda, Nirmal Kumar; Das, Anupam; Pramanick, Biswajit; Moulick, Debojyoti; Brestic, Marian; Raza, Muhammad Ali; Barutcular, Celaleddin; et al. (Molecules, 2020)
Declining rate of productivity and environmental sustainability is forcing growers to use organic manures as a source of nutrient supplement in maize farming. However, weed is a major constraint to maize production. A field study was carried out over two seasons to evaluate various integrated nutrient and weed management practices in hybrid maize. The treatment combinations comprised of supplementation of inorganic fertilizer (25% nitrogen) through bulky (Farmyard manure and vermicompost) and concentrated (Brassicaceous seed meal (BSM) and neem cake (NC)) organic manures and different mode of weed management practices like chemical (atrazine 1000 g ha−1) and integrated approach (atrazine 1000 g ha−1 followed by mechanical weeding). Repeated supplementation of nitrogen through concentrated organic manures reduced the density and biomass accumulation of most dominant weed species, Anagalis arvensis by releasing allelochemicals into the soil. But organic manures had no significant impact on restricting the growth of bold seeded weeds like Vicia hirsuta and weed propagated through tubers i.e., Cyperus rotundus in maize. By restricting the weed growth and nutrient removal by most dominating weeds, application of BSM enhanced the growth and yield of maize crop. Repeated addition of organic manures (BSM) enhanced the maize grain yield by 19% over sole chemical fertilizer in the second year of study. Application of atrazine as pre-emergence (PRE) herbicide significantly reduced the density of A. arvensis, whereas integration of mechanical weeding following herbicide controlled those weeds which were not usually controlled with the application of atrazine. As a result, atrazine at PRE followed by mechanical weeding produced the highest maize grain yield 6.81 and 7.10 t/ha in the first year and second year of study, respectively.